Influence of base plate preheating temperature on fatigue strength of AISI 4140 manufactured by laser powder bed fusion - Philipp Schüßler; Benjamin Dollhofer; Christian Krämer; Lukas Englert; Frauke Hinrichs; Volker Schulze; Stefan Dietrich (Journal of Materials Research and Technology)
This study investigates the influence of base plate preheating temperature on the fatigue performance of additively manufactured AISI 4140 steel, manufactured through laser powder bed fusion (PBF-LB). By varying preheating temperatures (150°C, 300°C, and 450°C), distinct microstructures – martensitic, mixed martensitic-bainitic, and fully bainitic – were achieved, each influencing fatigue strength and toughness. The results show that a fully martensitic structure provides superior fatigue resistance, while the mixed microstructure batch displayed reduced toughness and fatigue strength due to tempered martensite embrittlement (TME), which occurred at lower hardness compared to conventionally treated steels. However, the fully bainitic batch exhibited the highest toughness and a fatigue resistance between the two other batches, confirming that bainitic autotempering occurs at elevated temperatures, without evidence of embrittlement. Additionally, inherent porosity in AM samples acted as a stress concentrator, further reducing fatigue performance. This study highlights the importance of optimizing the base plate preheating temperature to control microstructure and porosity for enhanced fatigue performance in additively manufactured AISI 4140 components.